Detection of potentially pathogenic Arcobacter spp. in Bangkok canals and the Chao Phraya River - Noriko Tomioka; Wilasinee Yoochatchaval; Yasuyuki Takemura; Norihisa Matsuura; Tsuyoshi Danshita; Pornpawee Srisang; Noppamas Mungjomklang; Kazuaki Syutsubo (IWA Publishing, 2021)
The management of pathogenic bacteria in waterways is a public health issue. Here, we investigated the concentrations of potentially pathogenic bacteria, Arcobacter spp. and Campylobacter spp., and Escherichia coli, by quantifying species-specific genes in surface water samples from canals and the Chao Phraya River from June 2017 to June 2018 in Bangkok, Thailand. We assessed the relationship between the specific bacterial concentrations, water quality, and seasonal changes. Arcobacter spp. were detected at high density in all samples and showed seasonal fluctuations according to analyses based on 16S rDNA and the invasion gene ciaB. High levels of 16S rDNA and dut gene of E. coli were detected in the polluted drainage canals. A high correlation was observed between E. coli and chemical and biochemical oxygen demand (COD and BOD), suggesting that untreated domestic wastewater was the source of the E. coli. In contrast, Arcobacter spp. were detected with high density even in water samples with relatively low COD, suggesting that Arcobacter spp. are more likely than E. coli to survive in the water environment. The analysis of 16S rDNA and ciaB gene sequence analyses indicated that the Arcobacter spp. isolated from the drainage canals were A. butzleri and A. cryaerophilus. HIGHLIGHTS We conducted a survey of water quality and analyzed the concentrations of E. coli, Arcobacter spp., and Campylobacter spp. in canals in Bangkok.; Potentially pathogenic Arcobacter spp. were detected in particularly high levels in the heavily polluted canals.; Arcobacter spp. are likely to survive in the environment for longer periods than E. coli.;